Drebrin controls scar formation and astrocyte reactivity upon traumatic brain injury by regulating membrane trafficking - Juliane Schiweck (Nature Portfolio, 2021)
Reactive astrocytes control tissue damage following traumatic brain injury. Here the authors show that Drebrin (DBN) regulates scar formation and astrocyte reactivity in mice. Astrocytic DBN plays its neuroprotective role through the mediation of membrane trafficking.